2009
DOI: 10.2134/jeq2008.0054
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Natural Organic Matter in Long‐Term, Continuous‐Flow Experiments Simulating Artificial Ground Water Recharge for Drinking Water Production

Abstract: The role of biodegradation in the attenuation of natural organic matter (NOM) was investigated in long-term experiments that simulate artificial ground water recharge (AGR) for drinking water production. Lake water containing 5.8 mg L(-1) total organic carbon (TOC) was continuously fed into an 18.5-m-long sand column. During the 941 d of operation, on average 76 and 81% of TOC was removed within the first 0.6 m and the entire column length, respectively. Large molecular size fractions (approximately 1800-2200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Our TOC results fall into this range. Kolehmainen et al (2009) also reported a significant TOC removal in the infiltrated water in the first parts of the water-saturated zone in their experiments simulating the ARG process. In this respect, our observed TOC removal from the aquaculture farm effluent can be considered to be promising because this removal behaved quite similarly as that in the ARG plants with the retention time of 1.2 days.…”
Section: Experiments 2: Sand Filtration With Water-saturated Conditionsmentioning
confidence: 88%
See 1 more Smart Citation
“…Our TOC results fall into this range. Kolehmainen et al (2009) also reported a significant TOC removal in the infiltrated water in the first parts of the water-saturated zone in their experiments simulating the ARG process. In this respect, our observed TOC removal from the aquaculture farm effluent can be considered to be promising because this removal behaved quite similarly as that in the ARG plants with the retention time of 1.2 days.…”
Section: Experiments 2: Sand Filtration With Water-saturated Conditionsmentioning
confidence: 88%
“…In the ARG process, surface water (lake or river water), which contains higher dissolved organic carbon (DOC) concentration than is allowed in household water, is infiltrated through the sand and gravel layers by basin or sprinkling infiltration in order to form artificial groundwater. In this process, there is an efficient removal of DOC and particulate organic matter (Kolehmainen et al 2009;Lindroos et al 2002). For example in Finland, the DOC level of about 10 mg L −1 in the infiltrated lake water has been decreased to less than 2 mg L −1 in ARG (Lindroos et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In biodegradation NOM is degraded to dissolved inorganic carbon, which is not accumulated in the soil. On the other hand, in a column test by Kolehmainen et al (2009) only 50% of NOM removal was estimated to be due to biodegradation. According to this value, NOM accumulation by sorption and mechanical filtering in the aquifer is possible.…”
Section: Introductionmentioning
confidence: 95%
“…Studies on existing MAR sites and column tests have shown that the NOM content in infiltrated surface waters decreases rapidly, early on along the flowpath as the more easily degraded or adsorbable fraction is rapidly removed (Frycklund 1995;Grünheid et al 2005;Hiscock and Grischenk 2002;Kolehmainen et al 2009Kolehmainen et al , 2006Lindroos et al 2002;Niinikoski et al 2016). Hydrogeology (e.g., sediment porosity, permeability and groundwater flow), geochemical and nutrient conditions, temperature, and redox conditions are known to have an impact on the NOM removal rate in MAR (Maeng et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…When fully saturated, sand column tests were conducted, 76%-81% reduction of total organic carbon (TOC) was achieved. It was also reported that biodegradation accounted for 32%-52% of the dissolved organic carbon removal, with a conclusion that biodegradation has a key role in NOM removal in MAR [12].…”
Section: Introductionmentioning
confidence: 96%